Initiation characteristics of tight sandstone reservoir under different fracturing fluid infiltrations. Issue 1 (February 2021) - Zhang, Yin; Yu, Rangang; Yang, Wendong; Tian, Yong; Shi, Zhicheng; Sheng, Chengxiang; Sun, Hongyuan
Abstract: True triaxial hydraulic fracturing experiments were carried out on artificial analogue rock samples (AARS) of tight sandstone to analyze initiation characteristics under different fracturing fluid (FF) infiltrations. Moreover, the initiation was monitored by acoustic emission (AE) system. The results show that: FF fracturing has the lowest initiation pressure (37.7MPa) and average pressurization rate (0.2MPa/s), and takes the longest time for initiation (209s). Besides, AE signal is scattered and no extension appears after initiation. FF + temporary plugging agent (TP) fracturing has the highest initiation pressure (43.5MPa) which is lower than extension pressure, and it also has higher pressurization rate and amplitude peak as well as shorter time for initiation compared with FF fracturing. As for FF + sleeve fracturing and FF + nano-organo boron crosslinking agent (NBC) fracturing, they have much shorter time for initiation as well as higher evidently average pressurization rate and amplitude peak. Extension pressure is lower than initiation and almost all AE signal is concentrated at initiation moment.